Development of a new catalytic and sustainable methodology for the synthesis of benzodiazepine triazole scaffold using magnetically separable CuFe2O4@MIL‐101(Cr) nano‐catalyst in aqueous medium. (8th June 2020) - Gupta, Ajay; Sarkar, Fillip Kumar; Sarkar, Rajib; Jamatia, Ramen; Lee, Chang Yeon; Gupta, Gajendra; Pal, Amarta Kumar
Abstract : Magnetically retrieval CuFe2 O4 @MIL‐101(Cr) metal–organic framework was successfully prepared from easily available starting materials and characterized using various spectroscopic and analytical techniques such as powder X‐ray diffraction, scanning electron microscopy, energy dispersive X‐ray, transmission electron microscopy, elemental mapping, Fourier transform infrared spectroscopy, thermogravimetric analysis, X‐ray photoelectron spectroscopy, Brunauer–Emmett–Teller, vibrating sample magnetometer, and inductively coupled plasma optical emission spectroscopy. The catalyst was then used in the synthesis of benzodiazepines containing a triazole moiety in water. The advantages of this protocol include high yields, reusability of the catalyst, and gram‐scale synthesis. Abstract : A series of benzodiazepines containing triazole skeleton compounds were synthesized using magnetically separable CuFe2 O4 @MIL‐101(Cr) under sustainable conditions. The synthesized compounds were characterized by several spectroscopic techniques. The present protocol provides good to excellent yield of the products. Reusability and gram‐scale synthesis are some of the advantages of this protocol.